Impact of Transformational Leadership on Affective Commitment: Job Satisfaction as Mediator: https://doi.org/10.55966/assaj.2025.4.1.049 - Nazia Dildar; Dr. Tahira Nazir (`, 2025)
This research analyzes the impact of Transformational Leadership (TL) on Affective Commitment (AC). This study also finds out the mediating effect of Job Satisfaction (JS) on the connection of Transformational Leadership and Affective Commitment among employees working in Cement Industry across Punjab. The study is based on cross sectional data, which was collected through convenience sampling technique from a sample of 384 (trainee engineer, Staff, workers). Each variable was measured by using a five-point Likert scale. A total of 384 questionnaires were circulated, out of which 284 have been received showing 73% response rate. Data analysis has been performed using Smart PLS version 4.0 and statistical tools and techniques, such as Regression and Correlation have been performed. For demographics like age, gender and tenure SPSS software has been used. Results have obtained through structural equation modeling (SEM) depict a positive significant direct relationship between Transformational Leadership and Affective Commitment. A similar positive connection between Transformational Leadership and Job Satisfaction has also been found. However, any such positive, significant relationship also found positive. In mediation analysis, it has been found that job satisfaction mediates the relationship between Transformational Leadership and Affective Commitment. Manufacturing Sector of Pakistan has a need to adopt the concept of Transformational Leadership in order to improve Affective Commitment. Keywords: Transformational Leadership (TL), Job Satisfaction (JS), Affective Commitment